2023
DOI: 10.3389/fonc.2023.1116806
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum metabolome profile with the risk of breast cancer in participants of the HUNT2 study

Abstract: BackgroundThe serum metabolome is a potential source of molecular biomarkers associated with the risk of breast cancer. Here we aimed to analyze metabolites present in pre-diagnostic serum samples collected from healthy women participating in the Norwegian Trøndelag Health Study (HUNT2 study) for whom long-term information about developing breast cancer was available.MethodsWomen participating in the HUNT2 study who developed breast cancer within a 15-year follow-up period (BC cases) and age-matched women who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Most analyses in the HUNT2 21,22 study were reported by age groups or menopausal status and are described in the menopausal status paragraph.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most analyses in the HUNT2 21,22 study were reported by age groups or menopausal status and are described in the menopausal status paragraph.…”
Section: Resultsmentioning
confidence: 99%
“…Studies are generally conducted in Europe, 14,16,18,[21][22][23][24] the United States, 17,19,25 and Korea 15 and had variable sample sizes, spanning from 84 to 1,624 incident breast cancer cases. Most studies used a case-control approach nested within prospective cohorts.…”
Section: Metabolomics and Breast Cancer: Results From Prospective Epi...mentioning
confidence: 99%
See 3 more Smart Citations